Cyberpsychology : an introduction to human-computer interaction - Norman, Kent L. (Cambridge University Press, 2017)
"This textbook provides a comprehensive overview of the human-computer interface in clear, non-technical language, making it an ideal introduction for students of both psychology and computer science. Covering the past, present, and future developments in technology and psychology, it combines cutting-edge academic research with engaging illustrations and examples that show students how the material relates to their lives. Topics addressed include: human factors of input devices, and the basics of sensation and perception; memory and cognitive issues of users navigating their way through interfaces; communication via programming languages and natural speech interaction; cyberpathologies such as techno-stress and Internet addiction disorders; and challenges surrounding automation and artificial intelligence. This thoroughly updated second edition features new chapters on virtual reality and cybersecurity; expanded coverage of social media, mobile computing, e-learning, and video games; and end-of-chapter review questions that ensure students have mastered key objectives"--